Aggression as a Significant Factor in the Formation and Expression of the Self - Gihon, Anat (Bioenergetic Analysis, 2018)
Aggression, in the broad sense of the term, is examined from psychoanalytic literature with a focus on Bioenergetic theory and treatment. Clinical material enhances the exploration of working with aggression in patients, including energetic work with breath, grounding, boundary setting and expressive movements. This paper explores dealing with aggression when working with weaker structures, while working from a relational matrix and when encountering issues of countertransference.